The South African community pharmacy sector—an untapped reservoir for delivering HIV services - Nyamuzihwa, Tsitsi; Tembo, Angela; Martyn, Natalie; Venter, Francois; Maimin, Jacqueline; Houghton, Juliet; Lalla-Edward, Samanta Tresha (Frontiers in Reproductive Health, 2023)
Differentiated service delivery is recommended to improve the uptake of HIV testing and treatment for people living with HIV. One service delivery option yet to be fully capitalised on is community pharmacies. There are approximately 3,580 registered community pharmacies in South Africa. A total of 1,110 (31%) of these pharmacies are corporate chain pharmacies located in cities and towns, the remainder are individually owned, many of which are in less populated poorer settings. Community pharmacies traditionally play a pivotal role in providing health education to the populations they serve and are the first point of contact for people seeking health services, offering more convenient opening hours and shorter waiting times than public sector clinics or private doctors. As a result, patients regularly seek a variety of sexual and reproductive health services at community pharmacies such as self-testing devices for HIV, treatment for sexually transmitted diseases, and an array of reproductive health services, spanning emergency contraception to fertility advice, often signifying HIV risk. This has presented an opportunity for community pharmacies to provide access to HIV prevention and treatment to ensure the targets for HIV services set by international agencies and local government are achieved. Despite obstacles experienced with the expansion of the community pharmacist's role, exploring the potential of pharmacies to mediate the existing challenges with HIV service delivery has emerged as an important resource. Assessing the South African communities' specific HIV treatment needs and willingness to access HIV services from community pharmacies will benefit from additional research.